2013
DOI: 10.1080/09712119.2013.822814
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sun-dried garlic and psyllium seed on growth performance, carcass characteristics and serum biochemicals of broiler chicks fed tallow-containing diets

Abstract: One hundred and eighty 1-d-old broiler chicks were randomly assigned four dietary treatments. The first treatment group was fed a basal diet containing soya oil (Control-SO) but the other treatments were fed tallowcontaining basal diets supplemented with no medicinal plants (Control-T), 10 g/kg sun-dried garlic (SDG) or 10 g/kg psyllium seeds (PS). Growth performance in starter, grower and finisher periods, serum at 28-, 35-and 42-d-old and carcass characteristics at 42-d-old chicks were measured. Growth perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Moreover, researchers have demonstrated that garlic supplementation in broiler diets decreased cholesterol, triglycerides, and low-density lipoprotein (LDL) concentration (Ao et al, 2011;Dehkordi et al, 2010) as well as increased high-density lipoprotein (HDL), immunoglobulin M (IgM), IgG, and oxidative stability of meat (Choi et al, 2010;Ismail et al, 2021a) which are beneficial for human health. However, several studies reported that dietary garlic did not show any effect on broiler chickens' performance (Ao et al, 2011;Horton et al, 1991;Karimi and Ebadi, 2014). According to the benefits attributed to garlic diets, several modes of action have been proposed including a gut modulatory effect that influences positive changes in the microbial population, digestive enzyme secretion, and other metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, researchers have demonstrated that garlic supplementation in broiler diets decreased cholesterol, triglycerides, and low-density lipoprotein (LDL) concentration (Ao et al, 2011;Dehkordi et al, 2010) as well as increased high-density lipoprotein (HDL), immunoglobulin M (IgM), IgG, and oxidative stability of meat (Choi et al, 2010;Ismail et al, 2021a) which are beneficial for human health. However, several studies reported that dietary garlic did not show any effect on broiler chickens' performance (Ao et al, 2011;Horton et al, 1991;Karimi and Ebadi, 2014). According to the benefits attributed to garlic diets, several modes of action have been proposed including a gut modulatory effect that influences positive changes in the microbial population, digestive enzyme secretion, and other metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…The intensive production system depends on balanced compound diets where feed cost represents 65-70% of the total production cost of poultry farming. However, proper attention should be given to evaluate the nutritional quality of feed ingredients in order to supply the adequate amount of balanced diet for poultry to maximize the effective production cost (Panda et al 2014;Karimi & Ebadi 2014).…”
Section: Introductionmentioning
confidence: 99%